Հայ եկեղեցին և Հայոց կաթողիկոսարանի եկեղեցական քաղաքական կարգավիճակը ԺԲ դարում - Գևորգ սարկավագ Ալավերդյան (ՀՀ ԳԱԱ հրատ.)
Вместе с политическими изменениями в XII в. происходят также изменения и в Армянской Церкви. В результате распространения армянского народа по всему Ближнему Востоку и Балканам и нахождения Армянского Католикосата на перекрестках различных наций и религий, Армянский Католикосат получил совершенно новый церковно-политический статус. In the 12th century the Armenian Church experienced relocations parallel to the political moves of the time. As a result of the dispersion of the Armenian people throughout the entire Near East and the Balkans, and of the Armenian Catholicossate taking refuge at an international and inter-religious crossroad, the Armenian Catholicossate acquired a totally new status.
Keywords: History; B Philosophy; Psychology; Religion; BL Religion; D History